2021
DOI: 10.1177/10887679211028879
|View full text |Cite
|
Sign up to set email alerts
|

A Link between Psychopathy Affect and Instrumentality in Homicide

Abstract: This study tests the hypothesis that psychopathy is more associated with instrumental homicides than mixed and reactive homicides, and explores relationships between Psychopathy Checklist-Revised (PCL-R) facet/item scores and different forms of homicide: instrumental ( n = 130), mixed ( n = 103), and reactive ( n = 219) homicides. Instrumental homicides scored higher on facet 2 ( p < .01) but scored lower on facet 4 ( p < .1) compared to reactive homicides, whereas no facet scores differed between mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The analyses have demonstrated that Spanish perpetrators of femicide presented an average score in psychopathy of 14.4 points, which is a score similar to that found by other homicide [57] and femicide studies [22,59]. When taking into account the total score for classifying the killers of women as psychopaths or not, if the European cutoff point (25 points) is used, the percentage of subjects considered to be psychopaths ascends to 13.4%, but upon raising the cutoff point to 30, just 3 subjects (3.1%) could be considered psychopaths.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The analyses have demonstrated that Spanish perpetrators of femicide presented an average score in psychopathy of 14.4 points, which is a score similar to that found by other homicide [57] and femicide studies [22,59]. When taking into account the total score for classifying the killers of women as psychopaths or not, if the European cutoff point (25 points) is used, the percentage of subjects considered to be psychopaths ascends to 13.4%, but upon raising the cutoff point to 30, just 3 subjects (3.1%) could be considered psychopaths.…”
Section: Discussionsupporting
confidence: 65%
“…In this regard, the same study concluded that there may be individuals with high psychopathy scores involved in reactive homicides, but that this was not just due to an inability to anticipate the consequences, but rather that they may simply not attempt to suppress their violent behavior. Recently, Sohn et al [57] studied the relationship between psychopathy and homicide in a sample of 457 offenders convicted of homicide in South Korea. The subjects in the sample had a mean PCL-R score of 12.3 (median = 11).…”
Section: Homicide Femicide and Psychopathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that most research in forensic settings has focused on broad measures of crime (i.e., violent vs. non‐violent) and recidivism, less is known as to whether psychopathy shows more specific associations with different types of offending. In particular, while studies have examined the role of psychopathy in relation to certain crimes such as homicide (Fox & Delisi, 2019; Sohn et al., 2022), most research does not examine psychopathy's differential associations with varied offence categories (e.g. theft; driving offences) within the same study.…”
Section: Introductionmentioning
confidence: 99%